IMPLEMENTASI PEMBENTUKAN KARAKTER DAN INTEGRITAS MAHASISWA MELALUI PAK (PENDIDIKAN ANTI KORUPSI) - Ni Komang Ayu Sintia (Jurnal Ilmu Hukum Sui Generis, 2023)
Corruption can be simply defined as misuse of government funds for personal or group interests. The problem of corruption in Indonesia today is not just legal and political and needs to be addressed immediately. The active role of students in preventing corruption is expected to be more focused by participating in building an anti-corruption culture in the society. Students are expected to act as agents of change and drivers of anti-corruption movement in the society. To become agents of change, students must first develop their personality and integrity through anti-corruption education. The implementation of anti-corruption education aims to shape the anti-corruption character of students and develop their enthusiasm and capacity as agents of change in the life of society and state and free from the menace of corruption. If the structure of student character and integrity is matured, it will strengthen the anti-corruption culture. The purpose of compiling this article is to explore the understanding of anti-corruption values among students and the implementation of anti-corruption education in tertiary institutions, the relationship between character building and integrity with anti-corruption education, and the role of students in strengthening anti-corruption culture. The data collection technique used is a literature review technique that focuses on literature review of both online literature (magazines, newspapers, other online literature sources) and offline literature (books, documents).